Implementasi Standar Penilaian dalam Kurikulum 2013 di Sekolah Dasar - Ndaru Mukti Oktaviani; Isnaini Wulandari (Faculty of Teacher Training and Education, Musamus University, 2021)
Implementation of the curriculum 2013 in elementary schools still faces challenges for teachers. The results of discussions with elementary school teachers in the Kuningan area, West Java, revealed that teachers still have difficulty assessing learning outcomes, but it is not yet known exactly what the actual conditions are. It must be solved to ensure the improvement of the quality of education. The objectives of this study are (1) to describe the problems faced by teachers for the assessment standards in the implementation of the Curriculum 2013 in elementary schools, (2) to explain the factors that cause the problems of the assessment standards in the implementation of the Curriculum 2013 in elementary schools. The research method used in this research is descriptive qualitative. The research design used descriptive case study steps. The research subjects were teachers and elementary school students at SDN 1 Manis Lor, Jalaksana Sub-District, SDN 1 Purwawinangun, Kuningan Sub-District and SDN Dukuhdalem, Japara Sub-District, Kuningan District. Data collection techniques were used by using observation, interviews, and documentation studies. The data analysis used refers to the analysis of qualitative research data. The results of the study show that what causes teachers to have difficulty implementing the assessment standards in the curriculum 2013 are the many aspects that must be assessed and the assessment system that seems complicated. The factors that cause teacher difficulties in carrying out assessments from the curriculum 2013 are the lack of understanding and limited time in making assessment instruments that are by the conditions.